Low frequency variabilty of the Agulhas Current region in a numerical model - du Plessis, Kirsten Annette (Department of Oceanography, 2014)
The Agulhas region is known to be of global importance due to its role in the Global Meridional Overturning Circulation (GMOC) and regionally it can influence rainfall patterns and severe weather events. The long-term variability of the Agulhas region was analysed in relation to temperature, sea surface height (SSH) and velocity within the current using output from a regional ocean model. Validation of the model with in situ and satellite observed values for the temperature and SSH showed the modelled SSH results to be only marginally different from the satellite observed, while the temperature validation showed the modelled results to be over-estimating temperature across the region. Relatively weak trends existed in temperature and SSH for some parts of the Agulhas Current, most notably the retroflection region. There were also periods such as the 1960s and 1990s which were anomalously warm whereas the 1950s and 2000s were relatively cool. Analyses of these periods in terms of atmospheric changes throughout the Southern Hemisphere revealed some connections with El Niño - Southern Oscillation (ENSO), the Southern Annular Mode (SAM) and shifts in the wavenumber 3 or 4 pattern in the mid-latitude atmosphere